Success and Challenge When Returning to Clinical Practice: A Case Series in Anesthesiologist Re-Entry - Michael S. Green; Usama Iqbal; Christopher R. Hoffman; Parmis Green; Nielufar Varjavand (Anesthesiology Research and Practice)
Introduction. Anesthesiologists returning to clinical practice pose unique challenges for licensing and credentialing boards. Few institutions provide re-education. We describe the physician refresher/re-entry program at our College of Medicine. Methods. We launched the physician re-entry program in 2006. This individualized program re-educates physicians who left clinical practice for any reason and are seeking to return. We report results achieved for 12 anesthesiologists who successfully completed the course between August 2012 and February 2018. Results. Seven men and five women left their practices for various reasons, which included relocation, family or medical reasons, substance use, and burnout. None left practice for medical negligence. Range away from clinical activity was 0–10 years. Five had active licenses. Seven were US graduates and five were international. Nine of 12 achieved their goals. Of the 3 others, 1 did not pursue her goal, another did not obtain a residency, and the other just finished the program. Seven out of 9 (78%) achieved their goal within 1 year of course completion. Discussion. Despite our small sample size, our experience to successfully return inactive physicians to the workforce adds to the scant literature and experience in refreshing inactive physicians. Our trainees return to practice serving communities across the country and are now a pivotal part of the anesthesiology workforce. Thus, this program not only services individual physicians, but the whole community affected by their absence.